PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP PENGALOKASIAN BELANJA MODAL PADA PEMERINTAH DAERAH DI WILAYAH PROVINSI JAWA TENGAH - Singgih Heru Pramono, 12.05.62.0010 (Students Journal of Accounting and Banking, 2015)
The goals of this research are: To know how the Original Regional Revenue (PAD) against the local government capital expenditure allocation, to know the influence of the General Allocation Fund (DAU) against the local government capital expenditure allocation, to know how the Special Allocation Fund (DAK) against the local government capital expenditure allocation. The population used in this study of local government in the province of Central Java which has been publishing the financial statements in the fiscal year 2013, a total of 35 city and County. Research data are secondary data obtained from the literature books, legal regulations in force, the publication. Processing research analysis using computer software approach with the program SPSS for Windows version 7.0. The test results showed that the original Revenue areas, General Allocation Funds and funds allocation of Special effect significantly to capital expenditure budget allocatedKeywords: Revenue Budget Shopping Districts, The General Allocation Fund, A Special Allocation Of Funds, Capital Expenditures